2019
DOI: 10.3390/app9224940
|View full text |Cite
|
Sign up to set email alerts
|

Laser Processed Oxygen-Free High-Conductivity Copper with Ti and Ti–Zr–V–Hf Films Applied in Neutron Tube

Abstract: The laser processing method has proven to produce surfaces while ensuring a low secondary electron yield of oxygen-free high-conductivity copper (OFHC) samples, making it attractive for electron cloud mitigation in next-generation particle accelerators and neutron tubes. In this work, the laser processing method is proposed to OFHC targets for the first time, aiming to reduce the secondary electrons in the neutron tube. The secondary electron yields (SEYs) and the thermal conductivities of Ti film and quaterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Compared with Ti and Ti–Pd films with untreated OFHC substrates, the surface roughness and surface area of Ti and Ti–Pd films with laser-treated OFHC substrates were obviously increased. As reported in the previous studies, the thermal conductivity of Ti film with laser-treated OFHC substrates was 3.5–11.5% higher than the one with untreated OFHC substrates measured from 25 to 300 °C [ 26 ]. It can be speculated that the thermal conductivity of Ti and Ti–Pd films with laser-treated OFHC substrates is also higher than those with untreated OFHC substrates.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Compared with Ti and Ti–Pd films with untreated OFHC substrates, the surface roughness and surface area of Ti and Ti–Pd films with laser-treated OFHC substrates were obviously increased. As reported in the previous studies, the thermal conductivity of Ti film with laser-treated OFHC substrates was 3.5–11.5% higher than the one with untreated OFHC substrates measured from 25 to 300 °C [ 26 ]. It can be speculated that the thermal conductivity of Ti and Ti–Pd films with laser-treated OFHC substrates is also higher than those with untreated OFHC substrates.…”
Section: Discussionmentioning
confidence: 62%
“…This indicated that the surface of sample #2 was basically covered by Ti film, while the surface of sample #4 was basically covered by Pd film. It can be speculated that C, N, and O elements were mostly introduced during sample transferal in the air [ 26 ]. As shown in Figure 6 b, it can be seen that the O 1s peak and Pd 3p 3/2 peak overlapped.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-evaporable getters (NEG) technology was first invented at CERN in the 1990s [1] and are now widely employed in particle accelerators [2] the Tokamak fusion test reactor [3], field-emission display, vacuum packaged MEMS [4] and neutron tubes [5].NEG materials have become an integral component of many ultrahigh vacuum environments mainly due to their unique surface properties, which are conducive to achieving ultrahigh vacuum (UHV) of the order of at least 10 −8 Pa [6,7] by chemically adsorbing gas molecules on their surface. Heat needs to be applied to the NEG to allow the surface gas to residually diffuse into the bulk before it can have pumping performance; this process is called "activation".…”
Section: Introductionmentioning
confidence: 99%